Childhood cardiomyopathies: a study in tertiary care hospital of Kashmir - Shairgojri, Abid Ahmad; Mohiuddin, Khalid; Bashir, Amber; Jan, Muzafar (International Journal of Contemporary Pediatrics, 2021)
Background: Cardiomyopathy constitutes a group of diseases that directly affect the structural or functional ability of myocardium. They are the most common form of heart diseases that are inherited in children and responsible for sudden deaths in healthy young adults. The Aim of our study was to provide a detailed description of clinical profile, epidemiology and etiology of cardiomyopathies in children. Methods: This was a hospital based prospective observational study, conducted over a period of two and half years from September 2017 to March 2020 in the Post Graduate Department of Pediatrics Government Medical College Srinagar. Study group included all patients aged between 1 month and 18 years diagnosed with cardiomyopathy. They were subjected to a detailed clinical history and physical examination. All the patients underwent echocardiography. Results: During the study period 37 patients were diagnosed with different types of cardiomyopathies. Dilated cardiomyopathy was commonest seen in 19 (51.35%), followed by hypertrophic cardiomyopathy 13 (35%) cases. Fast breathing was most common presenting complaint in dilated cardiomyopathy while most of cases with hypertrophic cardiomyopathy were asymptomatic. There was one case of distinct form of cardiomyopathy isolated left ventricular hypoplasia. Males were more involved 21 (56.76%) cases. Majority of patients 18 (48.64%) were less than one year at time of diagnosis. Parental consanguity was seen in 6 (16.22%) cases. Underlying cause was identified in 10 (27.02%) cases with myocarditis being the commonest cause. Conclusions: Pediatric cardiomyopathy represents a considerable percentage of children with cardiac disorders. Dilated cardiomyopathy is the most common type usually presented with congestive heart failure, majority of cases of hypertrophic CMP were asymptomatic. Male preponderance was seen in dilated and hypertrophic cardiomyopathy. Parental consanguinity was seen in significant number of patients. Myocarditis and inborn error of metabolism was seen in significant number of patients.